Is an oritavancin catheter lock solution active against biofilms of staphylococci and enterococci? - Marta Díaz-Navarro; Emilia Cercenado; Ariadna Monte; Andrés Visedo; Carmen Rodríguez; Ma Jesús Pérez-Granda; Patricia Muñoz; María Guembe (Heliyon)
Background: Oritavancin (ORT) is a new single-dose lipoglycopeptide showing in vitro activity against staphylococci and vancomycin-resistant enterococci. However, there is no data regarding its potential use as a catheter lock solution are scarce. We constructed an in vitro model to analyze the efficacy and stability of an ORT lock solution against the biofilm of staphylococci and enterococci over 7 days at 37 °C. Methods: We used Staphylococcus aureus, Staphylococcus epidermidis, and vancomycin-susceptible Enterococcus faecalis ATCC strains. We performed a metabolic activity assay using a 2-mg/ml solution of ORT over a 7-day incubation period at 37 °C. The solution was tested against 24-h biofilms of each strain at day 0 and 7. Metabolic activity was measured using the XTT assay, and median absorbance obtained at 490 nm in the spectrophotometer was compared between day 0 and day 7. Results: The percentage reduction in metabolic activity was 95.3 % between biofilms treated with ORT solution incubated for 7 days and biofilms treated with ORT solution before incubation. Conclusion: Ours is a proof-of-concept study that shows ORT to be a potential treatment as a catheter lock solution for eradication of staphylococcal and E. faecalis biofilms. It is needed to further test ORT against more clinical strains and to compare its activity with other antimicrobials in a biofilm model.